STRUCTURE OF SOCIOECOLOGICAL AND ECONOMIC SECURITY OF ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article examines the existing approaches to the definition of the structure and essence of the components of socioecological and economic security. The socio-ecological and economic security of the enterprise is characterized by the protection of vital interests of the enterprise from possible threats, due to the reliable provision of all kinds of resources, formation and development of the economic potential of the enterprise, in which the probability of unwanted changes is smaller than the critical limit. At the same time, it is a state of stable preservation of the basic indicators and parameters of the company's operation, the ability to provide development, to achieve the goals, responding adequately to changes in the environment. The substantive content of the socioecological and economic security of the company clarifies its components, for the specification of which the resource and functional approaches are used. The scientific novelty of the research is to develop the theory of enterprise security, to summarize the results of existing developments, to improve approaches to the definition of the essence and meaningful content of the components of socioecological and economic security of the enterprise, implemented within a three-component approach using the decomposition method (the first level of decomposition – the  allocation of social, environmental and economic security enterprises, the second – consideration of the components of the social, environmental and economic security of the enterprise; the third level – definition content of the individual subsystems of social, environmental and economic security). The practical value of the results of the study is that the applied approaches focus on all the most important resources and activities of the enterprise, which gives the opportunity to obtain information for the adoption of sound management decisions. Such information will allow us to determine target installations for the development of the enterprise in the strategic perspective from the point of view of providing socioecological and economic security in general, tactical and operational levels – in the context of its individual components
Keywords: security, socioecological and economic security of the enterprise, structuring of the socioecological and economic security of the enterprise